2015
DOI: 10.1039/c4mb00747f
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic investigation of systemic manifestations associated with Alzheimer's disease in the APP/PS1 transgenic mouse model

Abstract: There is growing evidence that Alzheimer's disease may be a widespread systemic disorder, so peripheral organs could be affected by pathological mechanisms occurring in this neurodegenerative disease. For this reason, a double metabolomic platform based on the combination of gas chromatography-mass spectrometry and ultra-high performance liquid chromatography-mass spectrometry was used for the first time to investigate metabolic changes in liver and kidney from the transgenic mice APP/PS1 against wild-type con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 74 publications
2
27
1
Order By: Relevance
“…Animal studies support and advance these findings. Multivariate statistical analysis of metabolite profiles of the brain, liver, and kidney tissues from APP/PS1 and wild-type (WT) mice indicates systemic nature of AD-associated pathophysiology (52). Liver and kidney samples from 6-month-old mice were fingerprinted using a high-throughput multi-platform metabolomics approach based on gas chromatography/mass spectrometry and reversed-phase liquid chromatography.…”
Section: Load As a Systemic Metabolic Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies support and advance these findings. Multivariate statistical analysis of metabolite profiles of the brain, liver, and kidney tissues from APP/PS1 and wild-type (WT) mice indicates systemic nature of AD-associated pathophysiology (52). Liver and kidney samples from 6-month-old mice were fingerprinted using a high-throughput multi-platform metabolomics approach based on gas chromatography/mass spectrometry and reversed-phase liquid chromatography.…”
Section: Load As a Systemic Metabolic Disordermentioning
confidence: 99%
“…Liver and kidney samples from 6-month-old mice were fingerprinted using a high-throughput multi-platform metabolomics approach based on gas chromatography/mass spectrometry and reversed-phase liquid chromatography. Several observations pointed to the systemic character of the disorder with severely impaired glucose metabolism, mitochondrial dysfunction, and abnormal metabolism of BCAAs (52). Another longitudinal research performed in APP/PS1 transgenic and wild-type mice (6, 8, 10, 12, and 18 months of age) with deep profiling of the brain and plasma metabolome proved severely disturbed polyamines and BCAAs metabolism (53).…”
Section: Load As a Systemic Metabolic Disordermentioning
confidence: 99%
“…In contrast to classical biochemical approaches that focus on single metabolites or reactions, metabolomics and lipidomics approaches simultaneously identify and quantify hundreds to thousands of metabolites [1119]. Measurement of large numbers of metabolites enables network analysis approaches and provides means to identify critical metabolic drivers in disease pathophysiology [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous metabolomics studies in AD have reported alterations in lipid, antioxidant, and amino acid metabolism. However, results are not always unequivocal [11], [12], [13], [14], [15]. This is most likely due to differences in (analytical) methods, cohort selection, or context of use [16].…”
Section: Introductionmentioning
confidence: 99%